Abnormal eruption of teeth in relation to FGFR1 heterozygote mutation: a rare case of osteoglophonic dysplasia with 4-year follow-up - Yuchun Zou; Hanyu Lin; Weijia Chen; Lin Chang; Senxin Cai; You-Guang Lu; Linyu Xu (BMC, 2022)
Abstract Background We report a case and its 4-year follow-up of Osteoglophonic dysplasia (OD), a rare disease that disturbs both skeletal and dental development, which is usually caused by heterozygous FGFR1 mutations. Case presentation This article presents a case where a 6-year-old male patient suffered dysregulation of tooth eruption and was diagnosed with osteogenic dysplasia from a fibroblast growth factor receptor 1 (FGFR1) heterozygote mutation. However, the number of teeth is within the normal range, and their roots are well developed. Several interventions were implemented with varying degrees of results. The details of the 4-year follow-up showed that the signs of OD were more pronounced, including dwarfism, frontal bossing, delayed skeletal maturation, anteverted nares, micrognathia, and prominent ears, but the patient's impacted teeth and edentulous jaws remained unchanged. Conclusions FGFR1 heterozygote mutation and OD present significant difficulty for teeth eruption and subsequent intervention. Further measures ought to be taken in recognizing various symptoms presented by the patient. This case supports the significance of careful inquiry, comprehensive physical examination and correct diagnosis as indispensable steps for clinical practice in patients with unerupted teeth. Additionally, the detailed case and its 4-year follow-up length may provide new insights into osteogenic dysplasia and patients with impacted teeth while encouraging further exploration in treatment methods.